Silicon n-Channel Metal Oxide Semiconductor Field Effect Transistor Fabrication And Its Effect On Output Characteristics - Mohd Rashid, Mohd Marzaini (2012)

(untitled)
n-channel metal oxide semiconductor field effect transistor (n-MOSFET) fabrication requires specialized and expensive technologies such as ion implantation, chemical vapor deposition (CVD) and hazardous gases such as silane (SiH4), HCl and hydrogen. Low cost emulsion photomask with 35 μm channel length is used in this work. Fabrikasi transistor semikonduktor logam oksida kesan medan saluran n-silikon, “nchannel metal oxide semiconductor field effect transistor (n-MOSFET)” memerlukan teknologi khusus dan berkos tinggi seperti penanam ion, endapan wap kimia dan gas-gas berbahaya seperti silane, asid hidroklorik dan hidrogen. Topeng foto berkos rendah dengan lebar saluran 35 μm digunakan di dalam projek ini.